Batch Ingesting into EPrints Digital Repository Software. - Neugebauer, Tomasz; Han, Bin (Information Technology & Libraries, 2012)
This paper describes the batch importing strategy and workflow used for the import of theses metadata and PDF documents into the EPrints digital repository software. A two-step strategy of importing metadata in MARC format followed by attachment of PDF documents is described in detail, including Perl source code for scripts used. The processes described were used in the ingestion of 6,000 theses metadata and PDFs into an EPrints institutional repository.